Maternidade de Deus em Juliana de Norwich - Flores, Josué Soares (2013)
The next text is a Dissertation towards a Master Degree in the Faculty of Theology at The Pontifical Catholic University of the Rio Grande do Sul about The Maternity of God in Julian of Norwich, in tree acts: Maternity in Creation, Maternity in Incarnation and Maternity in Grace. The text rescues the importance of Julian s mystical thinking at XIV century context, and its relevance for: the ecclesiology, soteriology, creation and imago Dei doctrines. As well for the sacramental and anthropological and philosophical concepts, cosmology, cosmogony and theodicy concepts in medieval thinking. Julian of Norwich is an anchoress who lived c. 1343 - c . 1413, and wrote two versions of her visions known as Revelations of Divine Love popularly called Short Text and Long Text.